Enhanced efficiency in bifacial HIT solar cells by gradient doping with AFORS-HET simulation. (April 2018) - Yao, Yao; Xu, Xiaoyu; Zhang, Xiumei; Zhou, Haiping; Gu, Xiaofeng; Xiao, Shaoqing
Abstract: The paper presents a systematical simulation study of the influence of gradient doping of both emitter and back surface field layer on the photovoltaic (PV) performances of TCO/a-Si:H(p)/a-Si:H(i)/c-Si(n)/a-Si:H(n+)/TCO/Ag bifacial structure heterojunction with intrinsic thin layer (HIT) solar cells using AFORS-HET software simulation package. The gradient doping instead of uniform doping for emitter can promote the PV performance due to the presence of an additional electric field coming from the gradient doping, while the gradient doping of back surface field layer has negligible effect or negative influence on the cell performance compared to uniform doping, which can be explained by the varied energy band diagrams near the back junction interface. A final efficiency of 25.75% has been realized by using gradient doping of emitter with the same total doping amount as that of uniform doping case and uniform doping of back surface field layer for n-type bifacial HIT solar cells. This study can offer guidance on how to improve HIT solar cell efficiency beyond the world record value in experiment and how to achieve higher efficiency in mass production of HIT solar cells.